The Effectiveness of Law Enforcement Against Illegal Gold Mining Offenders in Jambi Province: A Fiqh Jinayah Perspective - Rafikah, Rafikah; Hasan, Hadri; Adawiyah, Robi'atul (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines law enforcement practices and their effectiveness in addressing illegal gold mining in Jambi Province, with additional analysis from the perspective of Fiqh Jinayah (Islamic criminal law). Employing an empirical juridical approach, the research was conducted in Sarolangun, Merangin, and Bungo Regencies. Informants included police officials from each region and individuals involved in illegal gold mining. Data were collected through observation, interviews, and document analysis, and analyzed via data reduction, display, and conclusion drawing. Findings reveal that law enforcement efforts begin with public education on environmental protection and the legal consequences of illegal mining. However, these efforts remain largely ineffective due to legal, structural, and socio-economic challenges. Contributing factors include the misalignment between laws and local realities, vague legal formulations, limited outreach, inadequate sanctions, and resource constraints faced by authorities. From the perspective of Fiqh Jinayah, illegal gold mining is categorized under Jarimah Ta’zir, allowing judge’s discretion in sentencing. Punishments can include imprisonment, fines, corporal penalties, or warnings, guided by principles of justice for both society and offenders. The study suggests that integrating Fiqh Jinayah may offer a culturally relevant alternative to enhance the deterrent effect and improve the overall effectiveness of law enforcement in this context.